Praktek Aplikasi Laporan Keuangan Menggunakan Microsoft Excel Pada Anggota Pengembangan Ekonomi Lokal (PEL) Kota Semarang - Agus Prasetyo; Wyati Saddewisasi; Andhy Tri Adriyanto (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
The practice of making financial reports based on Microsoft Excel for managing business processes for the Micro, Small and Medium Enterprises (UMKM) industry is very much needed. A very easy to understand Microsoft Excel-based bookkeeping system has now been created with the aim of helping business actors in obtaining effective and efficient financial reports. On this basis, time is needed to improve the ability of MSME business actors in Semarang City to use a Microsoft Excel-based financial reporting system to manage their business reports. The purpose of this training is to improve the business performance of partners, especially batik MSMEs who are members of the PEL in the city of Semarang. The capacity building of partners will be accommodated through the Community Service (PKM) program using face-to-face training methods. Partners who are members of the batik business center as training participants have received training to increase skills in using the manual bookkeeping system. Based on the problems above, the implementation of this service activity is by providing direct practice accompanied by discussions about the process of making Microsoft Excel-based financial reports which include mentoring, software improvements and direct operating practices. The implementation of this community service activity will be held in the even semester of 2021/2022. In this service, the output achieved is that partners can find out the benefits of the system and can use features to process their financial reports directly. Training participants can use a microsoft excel-based bookkeeping system to journalize every transaction, so that they can get financial reports quickly and efficiently.